PERTANGGUNGJAWABAN PLATFORM MEDIA SOSIAL INSTAGRAM SEBAGAI PENYEDIA LAYANAN IKLAN DALAM PERKARA PENIPUAN BERKEDOK ONLINE SHOP - Vengga Vengga; Ariawan Ariawan (Jurnal Hukum Adigama, 2021)
In this era, with rapid technological advancement, nowadays people can do trade and sell using liabilityonline system, especially on the social media which is Instagram Platform. Trades carried on Instagram have a risk, because dealing without meet face to face. By Juridical, do trade and sell on Instagram is not correct/safe. So that’s why legal certainty of liability on platform provider is essential in order to protect the consumer. If the consumer got losses, legal efforts are required to ensure consumer rights. Referring to the issue, the writer conducted research using the normative method and also did interview with several sources. The result from research, shows that liability of the platform provider in the positive law of Indonesian remains inadequate and is needed in the renewal of certain legal regulation. The institutions with authority on consumer cases be supposed to always inform information about consumer right so the consumer can understand the incumbency of the consumer. Reform into laws that regulate electronic transactions is needed in order to protect consumers while doing transactions electronic.